Expression and clinical significance of HOXA5, E-cadherin, and β-catenin in cervical squamous cell carcinoma - Pei, Lei (Int J Clin Exp Pathol, 2018)
Objectives: HOXA5 has been identified as a biomarker in pathogenesis of several cancers, such as non-small cell lung cancer (NSCLC) and breast cancer cells. The role has not been explored in cervical squamous cell carcinoma (CSCC). Methods: Tissues of 120 cases with CSCC and 30 controls with chronic cervicitis were constructed from our archived surgical pathology files and staining with HOXA5. Additional antibodies to E-cadherin and β-catenin were stained for comparison. For each marker, low expression was defined as staining score 0 to 3 points, whereas high expression referred to 4 points and above. Fifty-four patients in this research with cervical cancer were followed up for prognostic assessment. Result: HOXA5 had high expression in chronic cervicitis and low in CSCC (P=0.004). The positivity rates of HOXA5 in patients without muscular layer invasion (MLI) and lymphatic invasion (LI) was higher than that in metastasis (113 vs. 17; 117 vs. 3). Consistently, low expression of HOXA5 was more common in poorly differentiated carcinoma, CSCC subjects without MLI and LI. Expression of E-cadherin and β-catenin was parallel with the expression of HOXA5. Additionally, patients with higher expression of HOXA5 had much more favorable prognosis than those with lower expression among follow up of the 54 patients. Conclusion: In parallel with E-cadherin and β-catenin, low expression of HOXA5 was more common in CSCC patients with poor differentiation, without MLI and LI, among those which showed poor prognosis.